2007
DOI: 10.1007/s00024-007-0251-2
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a Dynamic Rupture on a Fault Plane with Short Frictionless Fault Branches

Abstract: Spontaneous bilateral mode II shear ruptures were nucleated on faults in photoelastic Homalite plates loaded in uniaxial compression. Rupture velocities were measured and the interaction between the rupture front and short fault branches was observed using high-speed digital photography. Fault branches were formed by machining slits of varying lengths that intersected the fault plane over a range of angles. These branches were frictionless because they did not close under static loading prior to shear rupture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…[33] As in the numerical investigations of Bhat et al [2007a] and the experimental studies of Biegel et al [2007] on the effects of short branches on rupture propagation, we find that rupture activation along the branch causes alterations in the rupture velocity on the main fault. Observations of rupture velocity during the 2001 Kunlun earthquake by Robinson et al [2006] and Vallée et al [2008] demonstrated that a small change in strike along the fault corresponds to a change in rupture velocity, with rupture accelerating after encountering a small angle kink to the extensional side, and rupture decelerating after encountering a small kink angle to the compressional side.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…[33] As in the numerical investigations of Bhat et al [2007a] and the experimental studies of Biegel et al [2007] on the effects of short branches on rupture propagation, we find that rupture activation along the branch causes alterations in the rupture velocity on the main fault. Observations of rupture velocity during the 2001 Kunlun earthquake by Robinson et al [2006] and Vallée et al [2008] demonstrated that a small change in strike along the fault corresponds to a change in rupture velocity, with rupture accelerating after encountering a small angle kink to the extensional side, and rupture decelerating after encountering a small kink angle to the compressional side.…”
Section: Discussionmentioning
confidence: 72%
“…Field observations indicate that the majority of earthquake ruptures propagate in the sub‐Rayleigh regime, but there are several cases with evidence of rupture apparently propagating in the supershear regime, such as the 1979 Imperial Valley [ Archuleta , 1984; Spudich and Cranswick , 1984], 1999 Izmit [ Bouchon et al , 2000, 2001], 2001 Kunlun [ Bouchon and Vallée , 2003; Robinson et al , 2006; Vallée et al , 2008], and 2002 Denali [ Ellsworth et al , 2004; Dunham and Archuleta , 2004; Aagaard and Heaton , 2004; Bouchon and Karabulut , 2008] earthquakes. Laboratory experiments involving mode II rupture along preweakened paths in Homalite plates have displayed definitive evidence of supershear rupture with clearly visible Mach fronts [ Rosakis et al , 1999; Rousseau and Rosakis , 2003, 2009; Xia et al , 2004, 2005; Biegel et al , 2007; Rosakis et al , 2007].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples for our experiments were made from square photoelastic Homalite 100 plates (15.25 cm × 15.25 cm × 1 cm) cut at an angle of 25° to form a fault as in the work by Xia et al [2004] and Biegel et al [2007] (Figure 2). Each sample had a 0.1 mm diameter hole at the center of the fault into which a nickel chromium wire was inserted before the samples were placed into a loading frame.…”
Section: Methodsmentioning
confidence: 99%
“…Still, laboratory tests show that perturbations through frictionless branches of the main crack line may slow down intersonic perturbation, and tensile wing cracks may also develop, Biegel et al (2007).…”
Section: Introductionmentioning
confidence: 99%